A cathodic photocorrosion-assisted strategy to construct a CdS/Pt heterojunction photocatalyst for enhanced photocatalytic hydrogen evolution. (24th May 2021) - Fan, Jianming; Xiong, Jinhua; Liu, Dayue; Tang, Yuanping; He, Song; Hu, Zhibiao
Abstract : A novel strategy based on the cathodic photocorrosion effect of CdS was developed to fabricate a CdS/Pt heterojunction photocatalyst, achieving a remarkable enhancement for H2 evolution. Abstract : A novel strategy was developed to fabricate a CdS/Pt photocatalyst (defined as CdS/w%Pt-PAR) via the cathodic photocorrosion effect of CdS. A tentative mechanism for Pt deposition on CdS via the cathodic photocorrosion effect was proposed, based on a series of electrochemical characterization methods, such as cyclic voltammetry and Mott-Schottky tests. Transmission electron microscopy verified that Pt was grafted on the CdS surface via a heterojunction. Moreover, a strong interaction between Pt and CdS was further confirmed by X-ray photoelectron spectroscopy. The optimal photocatalytic H2 evolution rate of CdS/2%Pt-PAR was 1086.1 μmol h −1, 6.4 and 2.6 fold higher than that of the reference samples synthesized by traditional photodeposition (CdS/2%Pt-PD) and chemical reduction (CdS/2%Pt-CR) methods, respectively. Linear sweep voltammetry and fluorescence experiments verified that CdS/2%Pt-PAR has a lower H2 evolution overpotential and faster separation of photogenerated carriers, respectively, compared with CdS/2%Pt-PD and CdS/2%Pt-CR. This work paves a new route for fabricating CdS/metal photocatalysts with highly efficient and stable photocatalytic H2 evolution activity.